P 85 Impaired pain processing on a brainstem level in patients with complex regional pain syndrome. (May 2022) - Thoma, P.; Drämel, N.; Fleischmann, R.; Lotze, M.; Grothe, M.; Strauss, S.
Abstract : Introduction: The complex regional pain syndrome (CRPS) is a chronic pain condition, which can follow limb trauma and is accompanied with sensorimotor dysfunction 1 . Current pathophysiological concepts assume local inflammatory processes that lead to peripheral and central sensitization of the nociceptive system 2 . Secondary maladaptive alterations of cortical sensorimotor excitability and disinhibition are well-established but little is known about the contribution of the brainstem. Preliminary evidence for altered brainstem excitability to trigeminal afferent stimulation was recently provided 3, 4 . This study uses a more comprehensive assessment of the nociceptive blink reflex (NBR) to assess the interaction of brainstem excitability and habituation to painful stimuli. Methods : 14 CRPS patients (10 female, 53 ± 17.6 years) and 10 controls (HCs; 9 female, 52±18.3) received assessments of pain and the NBR (R2 component, 2 trials, 10 stimuli/trial, interstimulus interval 3-5s). The R2 area (R2a) and habituation (R2h; gradient of R2a against stimulus order) were measured for the stimulated/non-stimulated side (_s/_ns). Results : Pain levels were 5, 0±1, 5/10 at rest and 7, 2±2, 1/10 during movements. ANOVA revealed a significant group effect for patients vs. controls (F=4.0; p=0.015). Post hoc tests were corrected for multiple comparisons and showed exceeding excitability (R2a_s: t=2.42, p=0.048; R2a_ns: t=2.98, p= 0.028) and impaired habituation (R2h_s: t=2.45, p=0.044; R2h_ns t=2.60, p=0.036). No significant associations of both disease duration and pain levels with NBR measurements could be obtained. Discussion : We here provide first evidence of altered NBR excitability and habituation indicating altered pain processing on a brainstem level. These results complement previous findings by demonstrating disinhibition as a source of increased brainstem excitability to painful stimulation remote from the limb directly affected by CRPS 4 . Future investigations are needed for a better understanding of the brainstem and its role in the pathophysiology of CRPS. The potential of the NBR as clinical biomarker, as it has been demonstrated in other pain diseases, should also be clarified in further investigation 5 . Literature: 1 Veldman PH et al. Signs and symptoms of reflex sympathetic dystrophy: prospective study of 829 patients. Lancet 1993. 2 Eldufani J et al. A medical mystery of CRPS. Heliyon. 2020. 3 Thiele A, et al. Treatment with calcitonin gene-related peptide antibodies modifies brainstem excitability and habituation to nociceptive trigeminal stimulation in migraineurs. CEPHALALGIA. 2021. 4 Drummond P et al. The Source of Hemisensory Disturbances in CRPS, The Clinical Journal of Pain: 2021. 5 De Marinis M et al. Decreased habituation of the R2component of the blink reflex in migraine patients. Clinical neurophysiology. 2003.